Characterization of SiO2 nanoparticles by single particle-inductively coupled plasma-tandem mass spectrometry (SP-ICP-MS/MS). Issue 11 (27th September 2017) - Bolea-Fernandez, Eduardo; Leite, Diego; Rua-Ibarz, Ana; Balcaen, Lieve; Aramendía, Maite; Resano, Martín; Vanhaecke, Frank
Abstract : The development of an ICP-MS/MS method for interference-free Si determination allows for chemical characterization of SiO2 nanoparticles. Abstract : The increase in the use of SiO2 nanoparticles (NPs) is raising concern about their environmental and health effects, thus necessitating the development of novel methods for their straightforward detection and characterization. Single particle ICP-mass spectrometry (SP-ICP-MS) is able to provide information on the size of NPs, their particle number density and mass concentration. However, the determination of Si via ICP-MS is strongly hampered by the occurrence of spectral overlap from polyatomic species ( e.g., CO + and N2 + ). The use of tandem ICP-MS (ICP-MS/MS) enables interference-free conditions to be obtained, even in the most demanding applications. Upon testing several gases, the use of CH3 F (monitoring of SiF +, mass-shift approach) and of H2 (monitoring of Si +, on-mass approach) were demonstrated to be the most suitable to overcome the spectral interference affecting ultra-trace Si determination (LoD < 15 ng L −1 ). By using these approaches, SiO2 NPs (ranging between 80 and 400 nm) can be detected and characterized. For SiO2 NPs > 100 nm, it was possible to provide accurate results in a straightforward way, as the signals they give rise to are well resolved from those of the background. In the case of 80 and 100 nm NPs, the use of a simple deconvolution approach following a Gaussian model was needed to characterize SiO2 NPs apparently showing incomplete distributions as a result of the presence of the background signal. Overall, the methods developed using SP-ICP-MS/MS are sensitive and selective enough for the interference-free determination of Si at ultra-trace levels, also in the form of SiO2 NPs.